Evaluasi Pelaksanaan Sekolah Sehat di TK Negeri Pembina 2 Merangin - Elsa Dwi Saputri; Puspita Sari; Muhammad Rifqi Azhary; Oka Lesmana S; Herwansyah Herwansyah (Pusat riset dan Inovasi Nasional, 2025)
This study aims to evaluate the implementation of the Healthy School program at TK Negeri Pembina 2 Merangin based on school sanitation standards. The evaluation focused on three main aspects: the availability and quality of facilities, the habituation of clean and healthy living behavior (PHBS), and school sanitation management. This research used a qualitative descriptive method with a case study approach. Informants included school principals, teachers, UKS officers, the Education Office, the Health Office, and parents. Data collection techniques included in-depth interviews, observations, and documentation. The results showed that while most sanitation facilities were available, they did not fully meet the standards. PHBS habituation was initiated but not evenly distributed. Managerial support from the school, especially budget allocation for facility maintenance and health education, needs improvement. This evaluation provides valuable input for schools and local governments to improve school sanitation policies.